VEGF receptor‐1 modulates amyloid β 1–42 oligomer‐induced senescence in brain endothelial cells. Issue 3 (21st December 2018) - Angom, Ramcharan Singh; Wang, Ying; Wang, Enfeng; Pal, Krishnendu; Bhattacharya, Santanu; Watzlawik, Jens O.; Rosenberry, Terrone L.; Das, Pritam; Mukhopadhyay, Debabrata
ABSTRACT: Aggregated amyloid β (Aβ) peptides in the Alzheimer's disease (AD) brain are hypothesized to trigger several downstream pathologies, including cerebrovascular dysfunction. Previous studies have shown that Aβ peptides can have antiangiogenic properties, which may contribute to vascular dysfunction in the early stages of the disease process. We have generated data showing that brain endothelial cells (ECs) exposed to toxic Aβ1‐42 oligomers can readily enter a senescence phenotype. To determine the effect of Aβ oligomers on brain ECs, we treated early passaged human brain microvascular ECs and HUVECs with high MW Aβ1‐42 oligomers (5 µM, for 72 h). For controls, we used no peptide treatment, 5 µM Aβ1‐42 monomers, and 5 µM Aβ1‐42 fibrils, respectively. Brain ECs treated with Aβ1‐42 oligomers showed increased senescence‐associated β‐galactosidase staining and increased senescence‐associated p21/ p53 expression. Treatment with either Aβ1‐42 monomer or Aβ1‐42 fibrils did not induce senescence in this assay. We then measured vascular endothelial growth factor receptor (VEGFR) expression in the Aβ1‐42 oligomer‐treated ECs, and these cells showed significantly increased VEGFR‐1 expression and decreased VEGFR‐2 levels. Overexpression of VEGFR‐1 in brain ECs readily induced senescence, suggesting a direct role of VEGFR‐1 signaling events in this paradigm. More importantly, small interfering RNA‐mediated knockdown of VEGFR‐1 expression in brain ECs was able to prevent up‐regulation of p21 protein expression and significantly reduced induction of senescence following Aβ1‐42 oligomer treatment. Our studies show that exposure to Aβ1‐42 oligomers may impair vascular functions by altering VEGFR‐1 expression and causing ECs to enter a senescent phenotype. Altered VEGFR expression has been documented in brains of AD patients and suggests that this pathway may play a role in AD disease pathogenesis. These studies suggest that modulating VEGFR‐1 expression and signaling events could potentially prevent senescence and rejuvenate EC functions, and provides us with a novel target to pursue for prevention and treatment of cerebrovascular dysfunction in AD.—Angom, R. S., Wang, Y., Wang, E., Pal, K., Bhattacharya, S., Watzlawik, J. O., Rosenberry, T. L., Das, P., Mukhopadhyay, D. VEGF receptor‐1 modulates amyloid β 1–42 oligomer‐induced senescence in brain endothelial cells. FASEB J. 33, 4626–4637 (2019). www.fasebj.org